Challenges facing the cotton sector worldwide and in Africa - (:unkn) unknown (My University, 2023)
To prepare the roadmap for its ten-year research on the cotton sector, CIRAD worked with a number of stakeholders to identify the main challenges facing the sector in the coming years, both globally and in Africa in particular. This document presents the 35 challenges identified, grouped into 7 macro-challenges. Several of these challenges are global in scope, and international collaboration is needed to address them.
Keywords: African Research